The Anti-Yahweh Label laššāw’ in Jeremiah (PART 1) - Retief, C Wynand (Old Testament Essays, 2022)
The traditional stance is that לשׁוא in Jeremiah (2:30; 4:30; 6:29; 18:15 and 46:11) denotes futility, mostly translated as “in vain.” This study scrutinises the first three texts (Jer 2:30; 4:30 and 6:29) in an effort to substantiate and modify a recent hypothesis that this term is instead a reference to the god Baal, “The Vain/Worthless One.” Support for the said hypothesis is gained by (1) a tentative observation in the discussion of Jer 2:30 that שׁוא (futility, “in vain”) is apparently limited to wisdom literature, whereas the Jeremiah texts are part of a cultic-legal corpus within a covenantal setting where the lexeme consistently appears as the prepositional prefixed definite form לשׁוא and apparently refers to prohibited objects of worship; (2) a search for intertexual clues in Jer 4:30; and (3) alertness to recurring key words and chiastic patterns in the context of Jer 6:29. In the course of working through the relevant texts, the notion took shape that the preposition ל־ is –besides meaning “for, for the sake of” – a technical term indicating covenantal relationship.It therefore seems that לַשָּׁוְא is not only a pejorative reference to Baal but also a label of the contra and anti-Yahweh overlord/s (בעלים/בעל) in (illegal) covenant relation to Israel. https://doi.org/10.17159/2312-3621/2021/v34n3a16